Pengembangan Metode Pembelajaran Beyond Center And Circle Time (BCCT) Terhadap Perkembangan Motorik Anak Usia Dini - Hesti Hesti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The research was conducted to improve learning so that it is more useful to improve quality as an effort to create a better quality of education. The purpose of this study was to determine whether there was an effect of the Beyond Center And Circle Time (BCCT) learning model on motor development in children. The research on children's motor activities was carried out for 2 weeks, from November 1 to 13, the Academic Year 2021/2022 which lasted 12 (twelve) meetings in order to obtain accurate data. The first week and second week meetings were conducted with observations on children's learning and documentation, in order to obtain accurate data results. The research method used is the observation method. Data collection techniques used are observation and documentation. Assessment of child development is carried out by the teacher when the child is playing the Center. The assessment was carried out using the BB, MB, BSH, and BSB categories. Indicators of children are observed by learning at the play center using 4 playing steps. The data collection technique used is analysis, with research instruments, such as notes, documents and documentation.